TOR-TOR SIRITTAK HOTANG PADA MASYARAKAT SIMALUNGUN KAJIAN TERHADAP MAKNA SIMBOL - Dwi Retno Purnama Sari; RHD Nugraningsih (Gesture: Jurnal Seni Tari, 2018)
ABSTRACT Sirittak Hotang Dance is a dance from the Simalungun area whose movement describes the activities of searching for rattan forests. The purpose of this research is to describe the meaning of Sirittak Hotang Dance symbol on Simalungun Society. The theoretical basis used is the meaning of dance by Royce (2007: 213-214) reviewed by exploring the contents and areas of expression. In the content area, the meaning of dance is reviewed through the type of dance with respect to the meaning and meaning contained intentionally and unintentionally. In the expression area the meaning of dance is reviewed through channels used for the ongoing communication in dance, while the symbol area is reviewed based on the philosophy of Batak society that is the noble value of Habonaron Do Bona. It’s takes 3 months to do this research, from January 2017 until March 2017. The location of research is in Huta Block 5 Nagori Simalungun Tengkoh, Panombeian Pane Sub-district, Simalungun Regency. Data collection techniques in this study using descriptive qualitative, data collection techniques conducted by observation, literature study, interviews and documentation. The results ofSirittak Hotang's Dance research on the Simalungun Society study on the meaning of symbols in the content area, first reviewed by the theme of minitis dance in the form of motion, fashion, and expression. The two meanings are deliberately related to the purpose of dance, the development of dance movement creativity, held to strengthen the unity of the Simalungun community and the unintentional meaning of the message, the information of Simalungun traditional art. In the area of expression, meaning is viewed through the human body as a medium of motion. Visual visibility is related to the suitability of dance movements with imitated objects and mood generation, accompaniment of music as accompanist, and amplifier of atmosphere and touch of nature and agriculture. So that can be obtained in this research about Sirittak Hotang Dance. Sirittak Hotang Dance is one of the Dance that is shown at Rondang Bintang party to celebrate and devote the joy and gratitude. Sirittak Hotang Dance is one of the five of Usihan Dance composed to commemorate the difficulties experienced by the previous generations to look for rattan to meet the needs of everyday life. The dance has an entertaining function. Keyword :Sirittak Hotang Dance, Meaning of Symbol.